Increasing reports in Mimosa (Mimosoideae, Leguminosae) for the Brazilian Flora - Morales, Matias; Ribas, Osmar S.; Fortunato, Renee Hersilia (Sociedad Argentina de Botánica, 2019)
Five species of Mimosa for the Brazilian Flora are reported: M. strigillosa, M. leimonias, M. petraea, M. oligophylla, and M. barnebiana. The three first ones are registered from Mato Grosso do Sul, while the remainder are registered from Paraná and Rio Grande do Sul. Descriptions, illustrations, distribution maps and morphologic, geographic and ecological comments are included. Original descriptions of M. petraea and M. leimonias are expanded, including fruit characterization.